Updated Systematic Review and Meta-Analysis Delirium Prevalence in Iranian Hospitals’ Patients - Ali Erfani; Hashim Hamid Shabeeb; Yousef Asadoola Jamshidi; Nazila Ghoreishi Amin; Aminollah Vasigh (Archives of Anesthesia and Critical Care)
Background: Delirium is a clinical neuropsychiatric syndrome, the main characteristic of which is a disturbance of consciousness affecting the patient's psychological state, and various factors are effective in causing it. The aim of the study is the prevalence of delirium in Iran. Methods: This study investigated the prevalence of delirium in a group of patients hospitalized in Iranian hospitals. The search was including PubMed, Scopus, ISI, Science Direct, and Google Scholar search engines in Farsi and English languages. The researchers designed a checklist and then analyzed the extracted results using the CMA software. Results: This study's initial search yielded 766 articles, of which the initial screening eliminated 458. 98 articles were excluded from the study due to repetition in the search, and finally, 25 articles were included in the analysis stage. According to the findings, the overall delirium prevalence is 22% (CI: 16.8-28.3%), the overall delirium prevalence in heart surgery patients is 20.2% (CI: 12.7-30.6%), and the delirium prevalence in the elderly is 44.3% (CI: 20.7-70.8%). Conclusion: It is necessary to conduct preventive studies in this field to reduce this amount.